Four-color fluorescence in-situ hybridization is useful to assist to distinguish early stage acral and cutaneous melanomas from dysplastic junctional or compound nevus - Yumei Lai; Yan Wu; Ruping Liu; Aiping Lu; Lixin Zhou; Lin Jia; Xinting Diao; Zhongwu Li (BMC, 2020)
Abstract Background/objective Acral and cutaneous melanomas are usually difficult to accurately diagnose in the early stage, owing to the similarity in clinical manifestations and morphology with those of dysplastic nevus (DN). In this study, we aimed to evaluate the diagnostic value of four-color fluorescence in-situ hybridization (FISH) probes specific to the RREB1,CCND1,and MYB genes, and centromere of chromosome 6, in distinguishing DN and melanoma. Methods Fifty one DN and 58 melanoma cases were collected and tested with four-color FISH. Histological features were reviewed and concordant morphologic diagnosis by three pathologists was considered the golden criterion. Results Fifty DN and 59 melanoma cases, with 37 melanomas in situ and 22 melanomas in Clark level 2, were confirmed finally; among them, 42 (71.2%) cases were acral. A comparison of clinicopathological features between the two entities showed that several features were considerably more frequently observed in the melanoma group, including more mitotic figures, stratum corneum pigmentation, lymphocyte infiltration, cell atypia, successive or pagetoid melanocyte growth pattern in the epidermis, larger tumor size, and older age at diagnosis. FISH was positive in 3 (6.0%) DN and 56 (94.9%) melanoma cases according to Gerami's criteria. In distinguishing the two groups, the sensitivity of the four-color FISH was 94.9% and specificity was 94.0%.We found that CCND1 gain was the most sensitive, either in Gerami's or Gaiser's criteria. Further analysis showed that CCND1gain was more obvious in the acral group of melanoma. Conclusions We conclude that the four-color FISH test was highly sensitive and specific in distinguishing early-stage acral and cutaneous melanomas from dysplastic nevus in Chinese population, and the most sensitive criterion was the gain of CCND1.